Biological sequence of malign gastric ulcer - Sojo, Enrique; Estapé, Gonzalo (Cirugía del Uruguay, 1977)
Sone aspects of superficial ulcerated gastric cancer biology which is marked by its long evolution, are studied. It is the neoplasm most frequently diagnosed in this evolutive stage. Multiple observations indicate that this ulcerated superficial cancer may decrease in size of ulcerous component, and even form scar, only to ulcerate again due to peptic action.